If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(3s-5)-15=-3(8s+3)-3
We move all terms to the left:
-3(3s-5)-15-(-3(8s+3)-3)=0
We multiply parentheses
-9s-(-3(8s+3)-3)+15-15=0
We calculate terms in parentheses: -(-3(8s+3)-3), so:We add all the numbers together, and all the variables
-3(8s+3)-3
We multiply parentheses
-24s-9-3
We add all the numbers together, and all the variables
-24s-12
Back to the equation:
-(-24s-12)
-9s-(-24s-12)=0
We get rid of parentheses
-9s+24s+12=0
We add all the numbers together, and all the variables
15s+12=0
We move all terms containing s to the left, all other terms to the right
15s=-12
s=-12/15
s=-4/5
| F(x)=4x^2+16 | | -5=g-(-3) | | 4=4h+16 | | F(x+1)=2x-9 | | k−6)=15 | | 7(x+1)-3x=3(x-4)+20 | | 4x–2=22–8x | | 7/9=6/b-10 | | -x/6=4-(-2) | | 3/7x=2/7x+5 | | 2+4(x+3)=6 | | 2n-n/5=5 | | F(-7)=2x-9 | | 4/5y=—2 | | x2+16x+4=0 | | 3x-9+4=-30 | | 37=u6 | | 9c-18=7c | | 5u-35=10u-80 | | 8-x=3x-3-8x | | 0=-3p+4p | | -4/7k=28 | | c=4c-84 | | 3x-10=3-2x | | 32b+5=20−b | | x/7=—8 | | 11=n/9+1 | | -7k=-9–6k | | 6(x+3)+4=-14 | | 2t-84=t-31 | | 2x+9=9x-11 | | -15c+20=-20–20–20c |